2017
DOI: 10.1002/jcsm.12191
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beta‐adrenergic blockade with carvedilol on cachexia in severe chronic heart failure: results from the COPERNICUS trial

Abstract: BackgroundCardiac cachexia frequently accompanies the progression of heart failure despite the use of effective therapies for left ventricular dysfunction. Activation of the sympathetic nervous system has been implicated in the pathogenesis of weight loss, but the effects of sympathetic antagonism on cachexia are not well defined.MethodsWe prospectively evaluated changes in body weight in 2289 patients with heart failure who had dyspnoea at rest or on minimal exertion and a left ventricular ejection fraction <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 32 publications
1
65
0
2
Order By: Relevance
“…Furthermore, heart failure is often associated with cachexia which makes the interpretation of weight changes difficult. Additionally, cachexia might result in a loss of plasma proteins, reducing plasma oncotic pressure, hampering plasma refilling from the interstitium . Additionally, weight loss during hospitalization is not necessarily associated with improved in‐hospital or post‐discharge morbidity or mortality, however weight gain has been associated with poor outcome .…”
Section: Congestion In Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, heart failure is often associated with cachexia which makes the interpretation of weight changes difficult. Additionally, cachexia might result in a loss of plasma proteins, reducing plasma oncotic pressure, hampering plasma refilling from the interstitium . Additionally, weight loss during hospitalization is not necessarily associated with improved in‐hospital or post‐discharge morbidity or mortality, however weight gain has been associated with poor outcome .…”
Section: Congestion In Heart Failurementioning
confidence: 99%
“…Additionally, cachexia might result in a loss of plasma proteins, reducing plasma oncotic pressure, hampering plasma refilling from the interstitium. 18,19 Additionally, weight loss during hospitalization is not necessarily associated with improved in-hospital or post-discharge morbidity or mortality, however weight gain has been associated with poor outcome. 20,21 Therefore, the European Society of Cardiology (ESC) guidelines for the diagnosis and treatment of acute and chronic heart failure recommend to distinguish acute fluid redistribution from true volume overload in patients presenting with congestion (no class recommendation).…”
Section: Definition and Mechanisms Of Congestionmentioning
confidence: 99%
“…Subjects with cardiac cachexia show higher rates of atrial fibrillation, possibly contributing to the higher mortality. In patients with severe CHF, the non‐specific beta‐blocker carvedilol has been shown to reduce the development and lead to a partial reversal of cachexia . Overall, standard heart failure medication seems to reduce not only cardiac cachexia but also has the potential to attenuate cachexia progression in cancer .…”
Section: Transition Of Sarcopenia In Chronic Heart Failure To Cardiacmentioning
confidence: 99%
“…In patients with severe CHF, the non-specific beta-blocker carvedilol has been shown to reduce the development and lead to a partial reversal of cachexia. 111 Overall, standard heart failure medication seems to reduce not only 494 cardiac cachexia but also has the potential to attenuate cachexia progression in cancer. 112 However, while the numbers of patients with cardiac cachexia have been lowered by heart failure medication, there is still a great medical need to find novel strategies for the sub-group of patients that seems to have no protection from developing cardiac cachexia by standard medication.…”
Section: Sarcopenia In Heart Failurementioning
confidence: 99%
“…Clinical studies have confirmed the metabolic ef-fects of non-selective blockers, such as propranolol, on reduced hypermetabolism in burns, which could be prolonged up to 2 years, and carvedilol, which attenuated the development and promoted a partial reversal of cachexia in patients with severe chronic heart failure, supporting a role for prolonged sympathetic activation in the genesis of weight loss. (62,63) CONCLUSIONS Catecholamine administration is useful and even life-saving for short-term restoration of tissue perfusion or correction of life threatening hypotension. However, catecholamines are poisonous when given in excess, causing regional ischemia, triggering arrhythmia and promoting systemic inflammation.…”
Section: Metabolic Effects Of β-Blockersmentioning
confidence: 99%